Revitalization of the Koperasi Keramat Dagang as an Economic Institution - Yumiati, Yumiati; Chandra, M Jeffri Arlinandes; Fitri, Rahma (Universitas Negeri Semarang, 2022)
Koperasi Keramat Dagang, which was established in 2004, has several problems such as organizational management, poor financial management and not optimal use of resources so that opportunities for cooperatives to develop are hampered and affect the welfare of members of the Koperasi Keramat Dagang in Kaur Regency. The purpose of this community service is to revitalize cooperatives so that poverty does not occur underdevelopment and with this revitalization the management of cooperatives can be even better. The methods used are lectures, discussions and questions and answers, training in organizational management and conducting simple bookkeeping training in cooperatives. The community service team began with friendly relations with cooperative management and deepening information about the problems that occurred at the Koperasi Keramat Dagang, after that the community service team conducted community service activities for management and cooperative members on 14-15 August 2020 and handed over Sea Products Management Equipment Grants .